The Euahlayi Tribe: A Study of Aboriginal Life in Australia - Parker, K. Langloh (Katie Langloh), 1856-1940; Lang, Andrew, 1844-1912 (Salt Lake City, UT : Project Gutenberg, 2003)
"The Euahlayi Tribe: A Study of Aboriginal Life in Australia" by K. Langloh Parker is a scientific publication written during the late 19th century. The book provides an in-depth exploration of the customs, beliefs, and social structures of the Euahlayi tribe, an Aboriginal group in north-western New South Wales. Parker draws from her extensive personal experiences and observations over two decades living among the Euahlayi, offering a detailed account of their folklore, totems, relationships, and spiritual beliefs. The opening of the work sets the stage for this ethnographic study by introducing the author's unique perspective as a close observer of the tribe's life. Parker discusses her history with the people, the genesis of her anthropological inquiries, and the broader context provided by previous researchers in the field. She emphasizes the richness of the Euahlayi's traditions, notably their intricate totemic system, marriage laws, and the central figure of Byamee, the All Father, who plays a significant role in their mythology and daily life. The narrative lays a foundational understanding of the cultural significance and spiritual life of the Euahlayi tribe, preparing readers for a deeper exploration of these topics in the ensuing chapters. (This is an automatically generated summary.)
Release date is 2003-03-01
Produced by Col Choat. HTML version by Al Haines.
Keywords: Euahlayi (Australian people)